Modification of endothelial nitric oxide synthase by 4-oxo-2(E)-nonenal(ONE) in preeclamptic placentas - Guerby, Paul; Swiader, Audrey; Tasta, Oriane; Pont, Frédéric; Rodriguez, Frédéric; Parant, Olivier; Vayssière, Christophe; Shibata, Takahiro; Uchida, Koji; Salvayre, Robert; Negre-Salvayre, Anne (Free radical biology & medicine, 2019)
Preeclampsia (PE) is a leading cause of pregnancy complications, affecting 3–7% of pregnant women worldwide. The pathophysiology of preeclampsia involves a redox imbalance, oxidative stress and a reduced nitric oxide (NO) bioavailability. The molecular and cellular mechanisms leading to the dysfunction of the placental endothelial NO synthase (eNOS) are not clarified. This study was designed to investigate whether aldehydes generated by lipid peroxidation products (LPP), may contribute to placental eNOS dysfunction in PE. The analysis of placentas from PE-affected patients and normal pregnancies, showed a significant increase in protein carbonyl content, indicative of oxidative stress-induced protein modification, as shown by the accumulation of acrolein, 4-hydroxynonenal (HNE), and 4-oxo-2(E)-nonenal (ONE) adducts in PE placentas. In contrast, the levels of these LPP-adducts were low in placentas from normal pregnancies. Immunofluorescence and confocal experiments pointed out a colocalization of eNOS with ONE-Lys adducts, whereas eNOS was not modified in normal placentas. LC-MS/MS analysis of recombinant eNOS preincubated with ONE, allowed to identify several ONE-modified Lys-containing peptides, confirming that eNOS may undergo post-translational modification by LPP. The preincubation of HTR-8/SVneo human trophoblasts (HTR8) with ONE, resulted in ONE-Lys modification of eNOS and a reduced generation of NO. ONE inhibited the migration of HTR8 trophoblasts in the wound closure model, and this was partly restored by the NO donor, NOC-18, which confirmed the important role of NO in the invasive potential of trophoblasts. In conclusion, placental eNOS is modified by ONE in PE placentas, which emphasizes the sensitivity of this protein to oxidative stress in the disturbed redox environment of preeclamptic pregnancies. [Display omitted] •Lipid peroxidation products accumulate in placentas from preeclampsia.•ONE-Lys adducts accumulate on eNOS in preeclamptic placentas.•Recombinant eNOS is modified by ONE on Lys residues.•ONE modifieseNOS and alters NO production in HTR8 trophoblasts.•The migration of HTR8 inhibited by ONE is restored by the NO donor NOC-18.